Kajian Kebijakan tentang Informasi dan Pelayanan Obat yang Mendukung Pengobatan Sendiri di Masyarakat - Sudibyo Supardi; Andy Leny Susyanti; Harimat Herdarwan (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Self-medication is the use of medicines by someone to treat pain complaints or self-recognizable symptoms and some chronic diseases that a doctor has diagnosed by. The purpose of the study is to obtain information about the problems and the role of pharmaceutical institutions in medicine information and services supporting self-medication in the community. The research design used a descriptive study in the form of policy studies and legislation related to medicine information and services in self-medication. Data sources are policies and legislation regarding medicine information and services regarding self-medication. The results of the study indicate: the problem of self-medication is there are no laws and regulations specifically regulate self-medication along with technical instructions on the role of each pharmaceutical institution. The problem with medicine information is that the central government program in providing medicine information has not been followed up by many district/ city health offices; people tend to buy medicines at retail in illegal medicine services facility, so they cannot read the information on the medicine packaging; and there are still many medicine advertisements in the mass media that have not provided objective and complete medicine information. The problem of medicine service policy is the lack of supervision, so that there are many illegal medicine service facilities in the community and lack of presence of pharmacy personnel in medicine information and services at pharmacies and drug stores. It is recommended that the Ministry of Health establish legislation and norms, standards, procedures and criteria for self-medication as a basis for government pharmaceutical institutions, private sector and professional organizations to support them. Abstrak Pengobatan sendiri adalah penggunaan obat oleh seseorang untuk mengobati keluhan sakit atau gejala yang dapat dikenali sendiri dan beberapa penyakit kronis yang pernah didiagnosis dokter. Tujuan kajian adalah mendapatkan informasi tentang permasalahan dan peran institusi farmasi dalam informasi obat dan pelayanan obat yang mendukung pengobatan sendiri di masyarakat. Rancangan penelitian menggunakan studi deskriptif berupa kajian kebijakan dan peraturan perundang-undangan terkait informasi obat dan pelayanan obat dalam pengobatan sendiri. Hasil kajian menunjukkan permasalahan pengobatan sendiri adalah belum ada peraturan perundangan yang khusus mengatur pengobatan sendiri beserta petunjuk teknis peran masing-masing institusi farmasi. Permasalahan dalam informasi obat adalah program pemerintah pusat dalam pemberian informasi obat belum ditindaklanjuti oleh semua Dinas Kesehatan kabupaten/kota; masyarakat cenderung membeli obat secara eceran di sarana pelayanan obat ilegal, sehingga tidak dapat membaca informasi pada kemasan obatnya; dan masih banyak iklan obat di media massa yang belum memberikan informasi obat yang objektif dan lengkap. Permasalahan dalam pelayanan obat adalah kurangnya pengawasan, sehingga banyaknya sarana pelayanan obat ilegal di masyarakat dan kurangnya kehadiran tenaga kefarmasian dalam informasi dan pelayanan obat di apotek dan toko obat. Disarankan agar Kementerian Kesehatan menetapkan peraturan perundangan-undangan dan norma, standar, prosedur, dan kriteria tentang pengobatan sendiri sebagai dasar bagi institusi farmasi pemerintah, swasta, dan organisasi profesi mendukungnya.